Future of the General Catalogue of Variable Stars from the Experience of Recent Name-lists - Samus Nikolay N.; Kazarovets Elena V.; Durlevich Olga V.; Kireeva Natalia N.; Pastukhova Elena N.; Khruslov Anton V. (Open Astronomy, 2021)
We briefly outline the history of the General Catalogue of Variable Stars (GCVS) and the New Catalogue of Suspected Variable Stars (NSV catalogue). Recently, we have completed a revision of the NSV catalogue. Positional information was checked for all its stars and, in many cases, new photometric data were added. As a result, one third of all NSV stars have been transferred to the GCVS. Having determined equatorial coordinates for variable stars in globular star clusters, we began to add them to the GCVS. Two Name-lists published so far contain more than 1700 variable stars in 36 globular clusters; an additional Name-list (about 900 variable stars in 27 globular clusters) will be published before the end of 2021. We discuss problem cases in the literature and in the Catalogue of Variable Stars in Galactic Globular Clusters revealed during our preparation of the Name-lists. The future of traditional catalogues of variable stars (GCVS; AAVSO Variable-star Data Index VSX) is discussed.